THE EIGHTH GRADE STUDENTS WRITING ABILITY OF DESCRIPTIVE TEXT AT SMPI NURUSSHOBAH MUMBULSARI - Nuriyandani, Aan; Ghozali, Imam; Sabartono, Ribut (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2022)
Teaching writing is an important way for communication and also it helps us develop, organize and reinforce our thoughts. This research reports on an analysis of the eighth-grade students’ writing ability of descriptive text at SMPI Mumbulsari. 24 students were chosen as the sample. The method used in this study was descriptive research. The data from this research was collected from a writing test. It was found that the ability of the students in writing the descriptive text was in a fair category from the score. Based on the result, 1 student (Excellent), 7 students (Good), 10 students (Fair), 5 students (Poor), 1 student (Very Poor). Meanwhile, having to Analyze the students’ ability in each aspect of writing, it can be said was not quite satisfying. It can be know from the students’ mean score categorized as fair, and the students’ score based on the five aspects of the mechanic was low. Keywords: ability, descriptive text, writing skill